Penerapan Strategi Kuis Siapa Aku dalam Meningkatkan Minat Siswa dalam Pembelajaran IPS di SMP - Ely Lubnah (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2022)
This study aims to determine the extent of the implementation of the who am I quiz strategy to increase student interest in social studies learning at SMP Negeri 5 Taliwang. The type of research used is Classroom Action Research (CAR) carried out in class IX of SMP Negeri 5 Taliwang. The research was carried out in collaboration with a Social Studies subject teacher for Class IX at SMP Negeri 5 Taliwang. The research subjects taken were class IX for social studies subjects, with a sample of 21 people, 10 men, and 11 women. On average, students have less ability because the school's input is lower middle NUN, and the level of student discipline is lacking. Based on the results of data analysis and research findings, it was concluded that the implementation of classroom action research carried out in class IX of SMP Negeri 5 Taliwang using the who I was quiz learning strategy was carried out in 2 cycles. In the first cycle, the results were not as expected, because students tended to be passive. After there is a good activity, in the implementation of the second cycle there is a very significant change in a very good direction, 75% more students have shown activeness in the learning process.